1998
DOI: 10.2190/tkkl-85xy-b2mf-7fyt
|View full text |Cite
|
Sign up to set email alerts
|

What is Happening to Injured Computer Users? A Study of CWA District 1 Members

Abstract: Using quantitative and qualitative data, this study sought to characterize the results of workers' compensation claims filed by CWA computer users in New York and New Jersey and document the perception of a small sample of workers living with these disorders. Most of CWA District 1's injured computer users in this study were diagnosed with carpal tunnel syndrome. The vast majority of the workers who have gone before a workers' compensation judge have been found to meet the criteria for a “permanent” disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This increase is consistent with findings in other jurisdictions. In the United States, researchers have noted either increases in accepted MSD claims (4,10,11) or a failure to reduce the number of successful MSD claims in jurisdictions where the numbers of other compensated injuries are down (12). Increased numbers of claims were noted in Canada (3) and in France, which witnessed a more than tenfold increase between 1987 and 1997 (13).…”
Section: The Sociolegal Context Governing Access To Compensation For mentioning
confidence: 99%
See 2 more Smart Citations
“…This increase is consistent with findings in other jurisdictions. In the United States, researchers have noted either increases in accepted MSD claims (4,10,11) or a failure to reduce the number of successful MSD claims in jurisdictions where the numbers of other compensated injuries are down (12). Increased numbers of claims were noted in Canada (3) and in France, which witnessed a more than tenfold increase between 1987 and 1997 (13).…”
Section: The Sociolegal Context Governing Access To Compensation For mentioning
confidence: 99%
“…Several studies have found that employers often contest compensation claims for MSDs and that compensation boards in Canada (3, p. 94) and boards and insurers in the United States (1,4) are often likely to refuse such claims. The workers are then forced to appeal their refusals, thus prolonging delays in access to compensation (and, in the United States, to medical treatment) for many years.…”
Section: The Sociolegal Context Governing Access To Compensation For mentioning
confidence: 99%
See 1 more Smart Citation
“…And they ignore the impact of work injuries on the relationships of workers and their children and spouses. These issues have been studied by a few non-economists [89][90][91], but they rarely reach the purview of policymakers and legislators. Studies describing the impacts of work injuries on specific people tend to portray injured workers in a much more favorable light.…”
Section: But Economistsmentioning
confidence: 99%
“…In Canada a recent report indicates that women are less likely to have contested claims for musculoskeletal disorders (MSDs) accepted by an appeals tribunal than their male counterparts ( Lippel 2003 ). The mislabeling and early mismanagement of these disorders may affect their clinical course ( Andersson et al 1995 ; Buckle 1997 ; Oschner et al 1998 ) and may have adverse consequences for women who balance multiple roles at home and work.…”
mentioning
confidence: 99%